Estimating the Causality and Elasticities of Residential Electricity Consumption for Malaysia - Othman, Nor Salwati; Hariri, Nurul Hezlin Mohamed (International Journal of Energy Economics and Policy, 2021)
The residential sector is the third-largest electricity user in Malaysia. A clear understanding of the rapid growth in its electricity consumption is crucial to the formulation of energy and environmental policy. This study applied the Autoregressive Distributed Lags, Vector Error Correction Model, and Variance Decomposition Approach in determining the long-run and short-run interaction between electricity consumption by residential sector and the suggested independent variables for 1980–2020 period. The selection of variables is based on the theory of demand. The outcomes confirmed the existence of a long-run relationship among variables. Also, the significant short-run elasticities of residential electricity consumption due to the changes in income and price. However, there is no significant short-run elasticity of residential electricity consumption due to the changes in occupancy and technology. In terms of causality interaction, results show the unidirectional causality running from electricity consumption, income, technology, and occupancy to electricity price in the long run; and the unidirectional causality running from income and occupancy to electricity price in the short run. The bidirectional causality also exists between electricity consumption and electricity price; and technology and electricity price in the short run. The research findings could be beneficial for policymakers in strengthening long-lasting economic policies. Keywords: residential electricity consumption, technology disruption, ARDL, Malaysia JEL Classifications: O1, O2, Q4, Q5 DOI: https://doi.org/10.32479/ijeep.11727